Navigating the Endodontic Challenge of a 40 mm Canine and Its Technical Adaptations - Siavash Moushekhian; Pooya Saeedi; Zoha Sahebnasagh (Case Reports in Dentistry)
Aim. The aim of this case report is to present the successful endodontic management of an abnormally long right maxillary canine diagnosed with symptomatic irreversible pulpitis, highlighting the technical adaptations employed during treatment. Summary. Technical adaptations included modifying the handle of the endodontic hand file and utilizing a side-vented microcannula for irrigation using positive and negative pressure technique. Despite the challenges posed by the abnormal tooth length, the procedure achieved a working length of 40.7 mm, and periapical radiography confirmed the master gutta-percha reaching full working length. Notably, the patient remained asymptomatic during the six-month follow-up, highlighting the efficacy of the treatment. This article also reviews the current literature, examining comparable cases and techniques documented in scholarly sources.